Effect of drama-education for alcohol/substance user on attitudes toward violence against women: randomized controlled design - Hümeyra Hançer Tok; Makbule Tokur Kesgin (BMC Public Health)
Abstract Background Alcohol is an important risk factor for substance abuse and violence against women. Educating alcohol users has become important in preventing violence against women. Objectives The aim of this study is investigate the impact of creative drama education on the attitudes of male patients with alcohol and substance dependence towards violence against women. Methods This study has a pre-test post-test parallel group randomized controlled design. This study as carried out at a treatment center for individuals with alcohol and substance addiction. The study was conducted with 35 male patients (Experimental group n = 18, Control group: n = 17) diagnosed with alcohol and substance addiction in a state hospital. Participants filled in the measurement tools before and after the training. Results Post-intervention, the experimental group showed statistically significant improvements in total ISKEBE scores (Z = − 3.421, p = 0.001, Cohen’s d = 1.44), as well as in the subdimensions of attitudes toward the body (Z = − 3.332, p = 0.001, d = 1.30) and identity (Z = − 3.075, p = 0.002, d = 1.18). No significant changes were observed in the control group (p > 0.05). Conclusion The findings suggest that creative drama education may have a beneficial effect on improving attitudes toward VAW among men with alcohol and substance use disorders. Further studies with larger and more diverse samples are recommended to confirm the generalizability and long-term impact of this approach. Clinical trial number NCT05595759-10/23/2022.